A Survey on Robotic Process Automation and its Importance in Digital Transformation - Syed Zaman Akhtar, Md Tabrez Nafis, Samar Wazir (International Journal of Advanced Science and Technology, 2020)
Digital transformation is not a one-off exercise or a single program. It’s a combination of multiple technologies that need to be carefully considered. For a successful execution, any digital transformation should be broken down into smaller initiatives and every such initiative should significantly optimize processes to provide benefits or efficiency gain while setting the stage for successful strategic digital transformation. RPA plays an important role and provides way to look at digital transformation in the easiest way without any heavy lifting implementations.  Keywords: Robotic Process Automation, RPA, IPA, COVID-19, Intelligent Process Automation, Process Optimization, Digital Transformation, Bots, Attended Bots, Unattended Bots.